Mrs. Root purchases tickets for a play - Rowe, Martin (photographer):::Creator::::::::::::
Photograph shows Mrs. Chester Root handing money to Mrs. Jack Gifford for tickets to a performance of the play "An Italian Straw Hat". The ticket reads: "The San Jose Y.W.C.A. presents San Jose Theatre Guild's premiere performance of [An] Italian Straw Hat Friday, June 21, 1963 Montgomery Theatre in Civic Auditorium Curtain 8:30 p.m. World Fellowship Benefit Donation $2.00." Mrs. Gifford is wearing a hat and is sitting on a high stool. There is a sketch to advertize the play on a bulletin board behind the women.